Science in non-hegemonic countries - Philippe Losego; Rigas Arvanitis (Revue d'anthropologie des connaissances)
What does non-hegemonic country mean? This dossier was indeed intended to deal with knowledge in “developing” countries. However, it tries to avoid the conventional enumeration of stigmas (poverty, illiteracy, epidemics, low investment and infrastructure, etc.) because these countries are not necessarily “por” but are dominated in the international division of scientific labour due to the lack of financial instruments capable of influencing the major trends in the production of knowledge in the world. It focuses on countries that are constrained by international trade but have room for manoeuvre to develop policy at the national level. It shows that while the globalisation of trade makes this policy difficult, it also gives it new legitimacy. We are witnessing a takeover of the scientific apparatus by the state in the name of globalisation in order to develop their own R&D policies.